Gambaran Calon Tenaga Kerja Gen Z (Studi pada Siswa SMA XYZ) - Seta A. Wicaksana; Nanda Putri Adhiningtyas (Fakultas Psikologi Universitas Tarumanagara, 2020)
The youngest generation - called Generation Z - was born and raised in completely different circumstances than the other, older generations. Although representatives of Generation Z have only just joined the labor market, there are already opinions and characteristics of them. This study aims to determine the profile (interests, intelligence, and personality) of XYZ Jakarta High School students as Z generation and provide an explanation of the profile candidate of the workforce needed in the industrial era 4.0. This research is a quantitative descriptive study that measures three variables, there are interests, intelligence, and personality. Retrieval of data using measurement tools compiled by the research team, there are Self Direct Search (measurement of interest), CFIT test by Raymond B. Cattel (measurement of intelligence), and New Big Five Inventory (NEO-PI-R) by McCrae and Costa (personality measurement) with a total of 506 items. Data was collected for two days with 243 subjects in class XII, consisting of 81 male students and 161 female students. The test results show that Investigative as the dominant interest of male students and Social as the dominant interest of female students, the intelligence of most students is medium level (average), and generally male and female students have a high level of neuroticism and extraversion and low level in openness, agreeableness and conscientiousness. Practically, this study will give insight to stakeholder (teachers, parents, and company) to give counseling and coaching program for generation Z of XYZ high school students to fulfil gap to the workforce profiles candidate needed in the industrial era 4.0